2018
DOI: 10.1186/s12974-018-1262-x
|View full text |Cite
|
Sign up to set email alerts
|

RAS modulation prevents progressive cognitive impairment after experimental stroke: a randomized, blinded preclinical trial

Abstract: BackgroundWith the aging population, the prevalence and incidence of cerebrovascular disease will continue to rise, as well as the number of individuals with vascular cognitive impairment/dementia (VCID). No specific FDA-approved treatments for VCID exist. Although clinical evidence supports that angiotensin receptor blockers (ARBs) prevent cognitive decline in older adults, whether ARBs have a similar effect on VCID after stroke is unknown. Moreover, these agents reduce BP, which is undesirable in the acute s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 55 publications
2
45
1
Order By: Relevance
“…Moreover, modulation of Ang II receptors had protective effects in a mouse cerebral malaria model as evidenced by reduced cerebral hemorrhages and increased survival, whereas AT2R-deficient mice were found to be more susceptible to cerebral malaria. Similarly, spontaneously hypertensive rats prone to middle cerebral artery occlusion (MCAO) and reperfusion showed decreased cognitive dysfunction, Aβ 1–42 cellular accumulation, and chronic-reactive microgliosis in brain tissue in the presence of continuous administration of AT2R agonist and AT1R blocker [ 62 ]. When treated with AT2R agonist at the time of reperfusion, MCAO rats showed preserved neurological function 24 h later [ 63 ].…”
Section: Endotheliummentioning
confidence: 99%
“…Moreover, modulation of Ang II receptors had protective effects in a mouse cerebral malaria model as evidenced by reduced cerebral hemorrhages and increased survival, whereas AT2R-deficient mice were found to be more susceptible to cerebral malaria. Similarly, spontaneously hypertensive rats prone to middle cerebral artery occlusion (MCAO) and reperfusion showed decreased cognitive dysfunction, Aβ 1–42 cellular accumulation, and chronic-reactive microgliosis in brain tissue in the presence of continuous administration of AT2R agonist and AT1R blocker [ 62 ]. When treated with AT2R agonist at the time of reperfusion, MCAO rats showed preserved neurological function 24 h later [ 63 ].…”
Section: Endotheliummentioning
confidence: 99%
“…Intervention trials in spontaneously hypertensive rats have shown reduced post-stroke cognitive impairment in rodents treated with RAS modifiers (specifically candesartan, an AT1R blocker). 192 The ongoing HEART phase 1B randomized controlled trial will evaluate the RAS system specifically, in nondemented adults at risk for AD, in which participants will be randomized to placebo vs one of two doses of telmisartan. 193 The optimal treatment regimen to prevent future cognitive impairment or dementia is difficult to ascertain, since nearly all antihypertensives have studies supporting their potential benefit.…”
Section: Class-specific Effects Of Antihypertensive Drugsmentioning
confidence: 99%
“…Studies have since had conflicting results with regard to the effect of C21 on CBF with some demonstrating no effect [ 193 , 264 ] while others suggest improvement [ 194 ], but BDNF mRNA and protein levels have been shown to be increased with C21 treatment post-stroke and this effect is absent with AT 2 R KO [ 193 ]. Further studies demonstrated that IP delivery of C21 after stroke induction, whether permanent or transient, improved outcome after stroke including in co-morbid animals with hypertension or advanced age [ 193 , 195 , [265] , [266] , [267] , [268] ] ( Table 2 ). Additionally, AT 2 R signalling with C21 has demonstrated further translational potential with promising results achieved with post-stroke oral delivery in female rats [ 269 ] or in a type 2 diabetes animal model [ 270 ], or with an intranasal delivery approach resulting in high levels detectable in the cortex and striatum, and improved outcome following stroke [ 271 ].…”
Section: At 2 R and Strokementioning
confidence: 99%
“…Mechanisms behind the beneficial effects observed with C21 induced AT 2 R signalling in experimental stroke have been attributed to reduced proinflammatory cytokines [ 262 , 264 ], reduced apoptosis [ 193 , 265 , 267 ], reduced ROS and oxidative stress [ 194 , 262 , 267 ], increased VEGF production [ 266 ], increased BDNF production [ 193 , 267 ], a switch from the M1 to M2 microglia phenotype [ 270 ], BBB stabilisation [ 194 , 262 ], and increased angiogenesis [ 267 ] ( Table 2 ). Some of these effects have been demonstrated to be dependent on IL-10 [ 195 ] or peroxisome proliferator-activated receptor-gamma (PPARγ) activation [ 194 ] ( Table 2 ).…”
Section: At 2 R and Strokementioning
confidence: 99%